Phylogenetic analysis and the spatial spread of arctic rabies virus in Chukotka - Sergey A. Chupin; Aleksandr D. Botvinkin; Ivan D. Zarva; Elena V. Chernyshova (Acta Biologica Sibirica)
Rabies is one of the most common zoonotic diseases of wild mammals in the Arctic. In this article we discuss possible ways of the rabies virus (RABV) incursion into the Chukchi Peninsula after the absence of animal rabies from 1991 to 2008. The aim of the current study is to analyze and document the genetic characteristic and spatial spread of the RABV on the Chukchi Peninsula in comparison with the same in Alaska and other Arctic territories and regions. For over 15 years the genetic diversity of the RABV in the Arctic has been the subject of intensive research. However, until recently, data with regard to the Chukchi Peninsula has been unavailable. An ongoing phylogenetic analysis of 14 full-sized N gene RABV isolates from the Chukchi Autonomous Region of the Russian Federation was carried out. The brain samples were collected from red foxes (9), arctic foxes (1) and dogs (4) in 2017–2024. It was found that all isolates belong to the Arctic genetic lineage. Among them two different pools were identified which demonstrate maximum nucleotide sequence identity with the Arctic-3 isolates from Greenland, the Svalbard Archipelago and Northern Canada. At the same time, different genetic sub-lineages (Arctic-3 v/s Arctic-2 and Arctic-4) were detected in neighboring land areas on both sides of the Bering Sea. A map demonstrating the transcontinental spread of RABV variants between Chukotka and Alaska was prepared based on our own and previously published data.